T315I clone selection in a Ph+ all patient under low‐dose ponatinib maintenance. Issue 8 (3rd July 2017) - Noetzli, Jasmine; Gavillet, Mathilde; Masouridi‐Levrat, Stavroula; Duchosal, Michel; Spertini, Olivier
Key Clinical Message: We report here the clinical course of a Ph+ ALL patient who was treated with ponatinib 15 mg/day, as maintenance therapy, and developed a BCR‐ABL T315I mutation leading to ALL relapse. This clonal evolution was reversed, without adverse effects, by increasing ponatinib to 45 mg/day. To our knowledge, we have been confronted with the first clinical case of a T315I clonal selection of ALL caused by subeffective therapeutic level of the drug. This single patient experience highlights the risk of T315I clone selection in Ph+ ALL treated with reduced dose ponatinib. Abstract : We report here the clinical course of a Ph+ ALL patient who was treated with ponatinib 15 mg/day, as maintenance therapy, and developed a BCR‐ABL T315I mutation leading to ALL relapse. This clonal evolution was reversed, without adverse effects, by increasing ponatinib to 45 mg/day. To our knowledge, we have been confronted with the first clinical case of a T315I clonal selection of ALL caused by subeffective therapeutic level of the drug. This single patient experience highlights the risk of T315I clone selection in Ph+ ALL treated with reduced dose ponatinib.